(untitled) (Research, Society and Development, 2025)
The growing concern for sustainability in the healthcare sector has fostered the development of eco-friendly alternatives, such as bamboo toothbrushes, in response to the environmental impact of plastic toothbrushes. Thus, this study aimed to assess perceptions regarding the disposal of manual plastic toothbrushes and sustainable practices related to the use of alternative devices like bamboo toothbrushes. A structured questionnaire was applied to 120 patients and companions at the School of Dentistry of Araçatuba (FOA-UNESP). Results showed that 67.5% of participants discard their toothbrushes immediately, with 98.3% of the disposals occurring in regular waste, demonstrating limited knowledge about the environmental damage caused by these products. Furthermore, none of the respondents used bamboo toothbrushes, and about 80% were unaware of their existence. Factors such as educational level, household income, and gender significantly influenced practices and perceptions regarding sustainable consumption. Therefore, it can be concluded that these results reinforce the need for educational campaigns to promote environmental awareness and the adoption of proper disposal and reuse practices for these materials, contributing to mitigating the environmental impacts associated with the use of these dental products.